Characterization of the epidemiological and clinical profile of cases of urban arboviroses transmitted by Aedes in Brazil, in the years from 2017 to 2021 (Research, Society and Development, 2023)
Arbovirus infections have increased dramatically over the last few years. The similar symptomatology in the initial phase of the disease makes the differential diagnosis and clinical management difficult. This study describes the epidemiological and clinical profile of cases of urban arboviruses transmitted by Aedes aegypti in Brazil from 2017 to 2021. A total of 1,145 human cases available in the Laboratory Environment Manager System (GAL) positive for Chikungunya viruses (CHIKV) were analyzed. (741/64.71%), Dengue virus (DENV) (381/33.27%) and Zika virus (ZIKV) (23/2%). Clinical and epidemiological information was obtained from the epidemiological investigation forms of the Notifiable Diseases Information System (SINAN). Most of those infected were female (63%), brown (31%) and aged between 31 and 40 years old. The most reported symptoms were fever (90%), severe arthralgia (67.3%), headache (53.2%), myalgia (52.8%) and rash (50%). During the acute phase (D0 to D6) it was observed that individuals infected with DENV had higher signs/symptoms than those infected with ZIKV and CHIKV. In the convalescence phase (D7 to >D15), the signs/symptoms of those infected with CHIKV increased and those with DENV and ZIKV declined. When considering the evaluation of signs/symptoms, an increased proportion (≥10%) was observed among those infected with CHIKV, signs/symptoms were present in an increased proportion later (D6 to >D15). The characterization of the clinical profile of arboviruses can direct the differential clinical diagnosis, as well as correlate the epidemiological aspects with the evolution of the disease.